1990
DOI: 10.2307/2061573
|View full text |Cite
|
Sign up to set email alerts
|

Rural-to-Urban migration and child survival in Senegal

Abstract: Analysis of the 1986 Senegal Demographic and Health Survey reveals that mothers may be able to improve their children's survival chances by migrating from the countryside to the city. Children of urban migrants, however, continue to experience a much higher risk of mortality before the age of 5 than children of urban nonmigrants, even after the mother has lived in the city for several years. This migrant mortality disadvantage persists when controlling for numerous socioeconomic and fertility-related factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
1
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 20 publications
2
83
1
5
Order By: Relevance
“…Cross-sectional studies have highlighted important differentials in infant and child mortality according to social, economic, and demographic factors, with ruralurban differentials among the most commonly examined. Previous studies that have focused on rural-urban mortality differentials for infants or children include Adetunji (1994), Brockerhoff (1990Brockerhoff ( , 1994Brockerhoff ( , and 1995, Defo (1996), and Sastry (1997). Until recently, most studies of intra-urban mortality differentials considered differences across groups defined according to social or economic characteristics (e.g., Timaeus and Lush, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies have highlighted important differentials in infant and child mortality according to social, economic, and demographic factors, with ruralurban differentials among the most commonly examined. Previous studies that have focused on rural-urban mortality differentials for infants or children include Adetunji (1994), Brockerhoff (1990Brockerhoff ( , 1994Brockerhoff ( , and 1995, Defo (1996), and Sastry (1997). Until recently, most studies of intra-urban mortality differentials considered differences across groups defined according to social or economic characteristics (e.g., Timaeus and Lush, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The exceptions are mostly focused on infant mortality. Brockerhoff (1990), and Ssengonzi, De Jong, and Stokes (2002) investigate the effects of female migration on the survival chances of their children in Senegal and Uganda, respectively. They find that rural to urban migration significantly increases children's survival chances.…”
Section: Health Outcomesmentioning
confidence: 99%
“…Urban to urban migration has continued to account for approximately 5% of the total migration since the increase in urbanisation during the 1960's.6 A majority of urban to urban migration is in the form of an upward movement through the urban hierarchy (as suggested in Ravenstein's Laws of Migration, 1885). [9] Brockerhoff [10][11][12] has used the results of Demographic and Health Surveys to analyse the relationship between mortality and rural to urban migration in Sub-Saharan Africa. The results confirm those of earlier epidemiological studies, which suggested that, migrants had higher mortality than urban natives and lower mortality than rural sedantes.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Successful adaptation to the urban environment depends not only on the behaviour and social mobility of the migrants, but also on the receptivity of the urban society. [11] Although our knowledge of the relationship between migration and health of women is increasing, we still have a limited knowledge of migration and health of women in the reproductive ages. [17 ]Also, there is a dearth of study, which tells about the health condition and knowledge of AIDS of migrant women according to the pattern of migration in India.…”
Section: Introductionmentioning
confidence: 99%